OXIDATIVE STRESS AND HIGH SENSITIVITY C-REACTIVE PROTEIN IN DIABETIC RETINOPATHY - DR. ROOPA P. KULKARNI; DR M.V.KODLIWADMATH (International Journal of Pharma and Bio Sciences, 2013)
Indians as an ethnic group have a higher risk of type 2 diabetes mellitus, most likely due to genetic susceptibility. Diabetic retinopathy is one of the most devastating microvascular complications of diabetes mellitus1 and it is the most common cause of blindness. Oxidative stress plays an important role in the pathogenesis of microvascular and macrovascular complications of diabetes mellitus2. High sensitivity C-Reactive Protein (hsCRP) is a significant marker of inflammation and plays an important role in the pathogenesis of diabetic retinopathy. Fasting blood samples were collected from healthy controls, diabetics without retinopathy and with retinopathy. Serum malondialdehyde (MDA), vitamin C and vitamin E were estimated as a marker of oxidative stress. Serum hsCRP was estimated to validate its usefulness in gauging the severity of diabetic retinopathy. Our study showed a significant increase in serum MDA and decrease in serum antioxidant vitamins in diabetic retinopathy as compared to diabetics without retinopathy (p<0.001). Our study demonstrated increased serum hsCRP in diabetics with retinopathy as compared to those without retinopathy (p<0.001). Our study clearly indicates a close relationship between oxidative stress and diabetic retinopathy. Supplementation of anti-oxidants may prevent or delay onset of diabetic retinopathy. Increased hsCRP in diabetic retinopathy points to its usefulness in risk stratification.